The effect of understory plants on pollinators visitation in coffee plantations: Case study of coffee plantations in West Bandung District, West Java, Indonesia - SUSANTI WITHANINGSIH; CLARISA DITY ANDARI; PARIKESIT PARIKESIT; NURULLIA FITRIANI (Society for Indonesian Biodiversity, 2018)
Withaningsih S, Andari CD, Parikesit, Fitriani N. 2018. The effect of understory plants on pollinators visitation in coffee plantations: Case study of coffee plantations in West Bandung District, West Java, Indonesia. Biodiversitas 19: 604-612. West Java is one of the excellent producers of the most expensive coffee in the world (Kopi Luwak). Coffee (Coffea spp.) is one of the crops that require insect pollination for fruit formation. Coffee production in Indonesia is declining in recent years despite the expansion of coffee cultivation area that increases by 2-5 times. The decline in coffee production has been associated with fewer visitations of pollinator insects. Visitations of pollinator insects can improve the quality and quantity of coffee, mainly from the abundance and diversity of pollinator insect. Abundance and diversity of pollinator insects can be improved by to providing them with flowering plants such as understory plants. This study aimed to prove the effect of the existence of flowering plants on the visitation of pollinator insects. Pollinator insects visiting coffee flowers were observed with an observation method in two observation units. The first unit was the location with understory plants while the second was the location without understory plants. The results showed that the abundance of pollinator insects visiting coffee flowers in unit 1 was significantly (P<0.05) higher than that in unit 2. However, the diversity of pollinator insects between the two locations did not differ significantly (P> 0.05).